Friday

July 25, 2014

July 25, 2014

Posted by **Kelli** on Friday, January 4, 2013 at 7:52am.

f(x)=x^4+2x^3-7x^2-8x+12

x=

f(x)=

- math -
**Reiny**, Friday, January 4, 2013 at 8:48amtry factors of 12

on the first try, I got f(1) = 0

so x-1 is a factor

by long algebraic or by synthetic division , I got

x^4+2x^3-7x^2-8x+12

= (x-1)(x^3 + 3x^2 - 4x - 12)

grouping the x^3 + 3x^2 - 4x - 12

= x^2(x+3) - 4(x+3)

= (x+3)(x^2-4)

= (x+3)(x+2)(x-2)

so

x^4+2x^3-7x^2-8x+12

= (x-1)(x-2)(x+2)(x+3)

(had I been patient, I would have found

f(2) = 0, f(-3)=0 and f(-2) = 0 as well)

the zeros are

1, 2, -2, -3

**Related Questions**

rational zeros theorem - Use the rational zeros theorem to find all the real ...

math - use the rational zero theorem to find all the real zeros of the ...

College algebra - Use the rational zeros theorem to find all the real zeros of ...

math - usethe rational zero theorem to find all real zeros of the polynomisl ...

college algebra - use rational zeros theorem to find all the real zeros in the ...

college algebra - use the rational zeros theorem to find all the real zeros of ...

College Algebra - Use the rational zeros theorem to find all the real zeros of ...

pre calculus - use the rational zeros theorem to find all the real zeros of the ...

calculus - use rational zeros theorem to find all the real zeros of the ...

college algebra - 1. solve the following logarithmic equation log_8(x+8)+log_8(x...